A Comprehensive Roadmap Towards the Generation of an Influenza B Reporter Assay Using a Single DNA Polymerase-Based Cloning of the Reporter RNA Construct - Kedia, Nandita; Banerjee, Saptarshi; Mondal, Arindam (Frontiers in Microbiology, 2022)
Mini-genome reporter assay is a key tool for conducting RNA virus research. But, procedural complications and lack of adequate literature pose a major challenge in developing these assay systems. Here, we present a novel yet generic and simple cloning strategy for the construction of influenza B virus reporter RNA template and describe an extensive standardization of the reporter RNP/ polymerase activity assay for monitoring viral RNA synthesis in an infection free setting. Using this assay system, we, for the first time showed the effect of viral protein NS1 and host protein PKC-Delta upon influenza B virus RNA synthesis. Additionally, the assay system showed promising results in evaluating the efficacy of antiviral drugs targeting viral RNA synthesis and virus propagation. Together, this work offers a detailed protocol for standardization of influenza virus mini-genome assay and an excellent tool for screening of host factors and antivirals in a fast, user-friendly and high throughput manner.